2021
DOI: 10.1097/inf.0000000000003088
|View full text |Cite
|
Sign up to set email alerts
|

High Rates of SARS-CoV-2 Family Transmission in Children of Healthcare Workers During the First Pandemic Wave in Madrid, Spain

Abstract: Background: Data on SARS-CoV-2 transmission among children living with healthcare workers (HCWs) are scarce. Methods: A cross-sectional study was performed at a tertiary Hospital in Madrid, including children of HCW who suffered from SARS-CoV-2 infection between March and May 2020. Children underwent enzyme-linked immunosorbent serological study for detecting SARS-CoV-2 antibodies: VIRCELL IgG assay. Results: One hundred thirteen children from 69 HCWs with confirmed SARS-CoV-2 infection were recruited: 47 chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Obesity has in fact been identified as a risk factor for COVID-19 disease severity [ 34 ]. A recent study reported high rates of SARS-CoV-2 infection among children living in high-risk places, presenting asymptomatic or mild disease [ 35 ], therefore, weight gain in children and adolescents could aggravate COVID-19 outcomes. Of note, the basal BMI did not correlate with the body weight gain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity has in fact been identified as a risk factor for COVID-19 disease severity [ 34 ]. A recent study reported high rates of SARS-CoV-2 infection among children living in high-risk places, presenting asymptomatic or mild disease [ 35 ], therefore, weight gain in children and adolescents could aggravate COVID-19 outcomes. Of note, the basal BMI did not correlate with the body weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…The strengths of our study include the online survey, which allowed us to quickly reach a sufficiently large sample of parents of children and adolescents, both in northern and southern Italy, during a period marked by strong restrictions on movement. Internet penetration stood at 83.7% in January 2021 in Italy [ 35 ] which contributed to the large number of people taking part in this survey [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…We detected a secondary attack rate of 27.3% in our study. In Spain, a survey among health care workers' children found a secondary attack rate of 43.7% [28]. In comparison, studies performed among health care workers' families in Amsterdam and China detected secondary attack rates of 10.98%, 18.8%, and 23.3% [29][30][31].…”
Section: Discussionmentioning
confidence: 96%
“…SARS-CoV-2 infection is frequently paucisymptomatic or even asymptomatic among children. Not surprisingly, serology-based studies including children have described seroprevalence rates higher than expected among children at risk, such as among children of healthcare workers (HCWs) [7]. However, longitudinal follow-up studies evaluating the dynamics of humoral response in the pediatric population are scarce, although some authors have observed important differences when comparing children and adults in terms of antibody titers [8].…”
Section: Introductionmentioning
confidence: 99%